Regeneration Roadmap: database resources for regenerative biology. Issue Volume 50:Issue D1(2022) (30th September 2021) - Kang, Wang; Jin, Tong; Zhang, Tao; Ma, Shuai; Yan, Haoteng; Liu, Zunpeng; Ji, Zhejun; Cai, Yusheng; Wang, Si; Song, Moshi; Ren, Jie; Hu, Baoyang; et al.
Abstract: Regeneration plays an instrumental role in biological development and damage repair by constructing and replacing cells, tissues, and organs. Since regenerative capacity declines with age, promoting regeneration is heralded as a potential strategy for delaying aging. On this premise, mechanisms that regulate regeneration have been extensively studied across species and in different tissues. However, an open and comprehensive database collecting and standardizing the abundant data generated in regeneration research, such as high-throughput sequencing data, remains to be developed. In this work, we constructed Regeneration Roadmap to systematically and comprehensively collect such information over 2.38 million data entries across 11 species and 36 tissues, including regeneration-related genes, bulk and single-cell transcriptomics, epigenomics, and pharmacogenomics data. In this database, users can explore regulatory and expression changes of regeneration-associated genes in different species and tissues. Regeneration Roadmap provides the research community with a long-awaited and valuable data resource featuring convenient computing and visualizing tools, which is publicly available at https://ngdc.cncb.ac.cn/regeneration/index .